aminat75u

2023-03-03

Find the roots of the quadratic equation $6{x}^{2}-x-2=0$.

Edwin Simmons

Beginner2023-03-04Added 6 answers

Solve for $x$:

The given equation is $6{x}^{2}-x-2=0$

$\Rightarrow $ $6{x}^{2}-4x+3x-2=0$

$\Rightarrow $$2x\left(3x-2\right)+1\left(3x-2\right)=0$

$\Rightarrow $ $\left(3x-2\right)\left(2x+1\right)=0$

$\Rightarrow $ $3x-2=0,2x+1=0$

$\therefore x=\frac{2}{3},-\frac{1}{2}$

Consequently, the given equation's roots are $\frac{2}{3}$ and $-\frac{1}{2}$.

The given equation is $6{x}^{2}-x-2=0$

$\Rightarrow $ $6{x}^{2}-4x+3x-2=0$

$\Rightarrow $$2x\left(3x-2\right)+1\left(3x-2\right)=0$

$\Rightarrow $ $\left(3x-2\right)\left(2x+1\right)=0$

$\Rightarrow $ $3x-2=0,2x+1=0$

$\therefore x=\frac{2}{3},-\frac{1}{2}$

Consequently, the given equation's roots are $\frac{2}{3}$ and $-\frac{1}{2}$.